Synthesis, Characterization and Antimicrobial Studies of Novel Derivatives of Phenol and Their Co(II), Ni(II), Cu(II) and Zn(II) Chloro Complexes - Abdul Jameel, A.; Syed Ali Padusha, M.; Sulthan Syed Ibrahim, K. (Asian Journal of Chemistry, 2010)
The synthesis, characterization and antimicrobial studies of Co(II), Ni(II), Cu(II) and Zn(II) complexes of N-[(5-amino-2-hydroxyphenyl)(phenyl)methyl]-N-phenylacetamide (PBA) and N-[(5-amino-2-hydroxyphenyl)(phenyl)methyl]nicotinamide (PBN) are reported here. Analytical methods such as TLC, melting point, magnetic and molar conductance and spectral studies such as IR, 1H NMR, 13C NMR, mass, electronic and EPR spectral studies were employed for the characterization. Analytical data show the composition of the metal complexes as [M(PBA)2(H2O)2] and [M(PBN)2(H2O)2] [M = Co(II), Ni(II), Cu(II) and Zn(II)]. Both the ligands and their metal complexes have been tested for in vitro to evaluate their activity against certain micro organisms.